Application of endospore-forming Bacillus species to food waste-recycling wastewater treatment: A focus on the fate of macromolecular nutrients. Issue 3 (June 2022) - Seo, Kyu Won; Gu, Man Bock; Tsang, Yiu Fai; Choi, Yong-Su; Chung, Jaeshik
Abstract: A novel bioprocess for treating high-strength food waste-recycling wastewater (FRW) by using endospore-forming bacteria was developed and evaluated under various hydraulic retention times (HRTs) and sequentially decreasing dissolved oxygen (DO) concentrations. Four Bacillus species (i.e., B. subtilis, B. licheniformis, B. mycoides, and B. thuringiensis ) were added to the laboratory-scale system operated for 200 days and fed with an influent of 30 g·BOD/L. The dominance of endospore-forming bacteria was achieved (> 65%) by adding Bacillus species, which decomposes macromolecular nutrients such as carbohydrates, proteins, and lipids. Longer HRT in the aerobic reactor led to a higher removal rate of organic matter, whereas endospore-forming bacteria were clearly identified in the anoxic reactor; the observed removal efficiency of carbohydrates, lipids, proteins, nitrogen, and phosphorus were 99.4%, 94.0%, 87.6%, 81.3%, and 91.4%, respectively, throughout the sequential aerobic-anaerobic reactors. The results show that the proposed system using endospore-forming Bacillus bacteria could be an effective alternative for high-strength FRW treatment. Graphical Abstract: ga1 Highlights: Predominance of endospore-forming bacteria in FRW was identified. Over 65% of Bacillus species were dominated under controlled DO and HRT. The macromolecular nutrients could be effectively decomposed. More than 88% of protein removal was achieved by endospore-forming bacteria.